New Cardiovascular Drugs: Patterns of Use and Association with Non-Drug Health Expenditures - G. Edward Miller; John F. Moeller; Randall S. Stafford (SAGE Publishing, 2005)
The potential role of new drugs in reducing expenditures for non-drug health services has received considerable attention in recent policy debates. We estimate expenditure models to determine whether the use of newer drugs to treat cardiovascular conditions is associated with lower (or higher) non-drug expenditures for these conditions. We fail to substantiate the findings of previous research that newer drugs are associated with reductions in non-drug expenditures. We find, however, that increases in the number of drugs used, or the mix of drugs of different ages, are associated with increased non-drug expenditures and find that the number or mix of drugs used are important confounders in the estimated association between drug age and non-drug expenditures.